1995
DOI: 10.1074/jbc.270.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Signaling during Insulin-stimulated Endocytosis of Its Receptor in Adipocytes

Abstract: Insulin causes rapid insulin receptor autophosphorylation, receptor endocytosis, and phosphorylation of its principle substrate (IRS-1). Using rat adipocytes, we studied the dynamics of receptor autophosphorylation, the kinase activity, and the IRS-1 phosphorylation state relative to the subcellular localization of these proteins. After 2 min of insulin exposure, the specific phosphotyrosine content of the insulin receptor in the internal membranes (IM) peaks at a level 5-6-fold higher than the plasma membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
81
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 47 publications
19
81
0
Order By: Relevance
“…As expected, insulin causes a redistribution of intracellular (LM and HM) GLUT4 to the cell surface (PM) (33). As we demonstrated previously by Western blotting (45), the insulin receptor undergoes ligand-dependent endocytosis, whereas caveolin shows a small insulin-dependent decrease in the LM as a result of apparent redistribution to the PM (37). The change in PM caveolin cannot be accurately measured because of the large amount of caveolin already at the cell surface.…”
Section: Methodsmentioning
confidence: 64%
“…As expected, insulin causes a redistribution of intracellular (LM and HM) GLUT4 to the cell surface (PM) (33). As we demonstrated previously by Western blotting (45), the insulin receptor undergoes ligand-dependent endocytosis, whereas caveolin shows a small insulin-dependent decrease in the LM as a result of apparent redistribution to the PM (37). The change in PM caveolin cannot be accurately measured because of the large amount of caveolin already at the cell surface.…”
Section: Methodsmentioning
confidence: 64%
“…In addition, similarly to what is occurring in cells expressing IR R252C , IRS 1 phosphorylation could be achieved by IR C860S localised mainly on microvilli supporting the idea that some IR biological signals can be elicited from these surface domains. However, endosome could also be a site of IR signal transduction and biological responsiveness, as suggested by studies of the kinetics of IR kinase activation and of the subcellular localisation of this kinase domain [18,19,20,42].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, under conditions where IR internalisation is inhibited (incubation at 4°C or expression of a dominant negative mutant of dynamin), IRS 1 is still phosphorylated [15,16,17], suggesting that IR internalisation is not required for the transduction of its biological signal. On the other hand, subcellular fractionation experiments (on 3T3-L1 adipocytes and rat hepatocytes) have shown that the pool of IR present on internal membranes undergoes a higher autophosphorylation in response to insulin than the IR present at the cell surface [18,19], and that IRS 1 is mainly distributed in intracellular compartments, probably endosomes, where it could be tyrosine phosphorylated in the presence of insulin [16,18,19,20]. These studies suggest therefore that IR signalling cascade takes place, at least in part, on endosomes and thus may require IR internalisation.…”
mentioning
confidence: 99%
“…fractions that also contain phosphorylated IRS 1. Tyrosine phosphorylation of IRS 1 in internal compartments, i.e LDM and cytosol, could be mediated by internalized insulin receptors [36], although tyrosine phosphorylation of IRS l occured in the LDM fraction even at 4 "C, which prevents insulin-receptor internalization [37]. In LDM, activation of PtdIns 3-kinase could result from the association of the enzyme already present in these fractions with tyrosine-phosphorylated IRS 1 and/or from the translocation of new molecules of PtdIns 3-kinase from the cytosol.…”
Section: Discussionmentioning
confidence: 99%